Line profiles and magnetic field in the x17.2/4B solar flare of October 28, 2003. Comparison of spectral observations in photospheric and chromospheric lines - Lozitskiy, V.G.; Lozitskaya, N.I. (Известия Крымской астрофизической обсерватории, 2008)
The exclusively powerful solar flare X17.2/4B of October 28, 2003 was observed by authors with the Echelle spectrograph of the horizontal solar telescope at the Astronomical Observatory of Kyiv Shevchenko’s National University.